2012
DOI: 10.1001/archgenpsychiatry.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between <emph type="ital">FKBP5</emph> and Childhood Trauma and Risk of Aggressive Behavior

Abstract: Context Childhood trauma may predispose individuals to aggressive behavior, and both childhood trauma and aggressive behavior are associated with hypothalamicpituitary-adrenal axis dysregulation. Objective To determine whether there would be an interaction between genetic variation in FKBP5 and childhood trauma in predicting aggressive behavior. Design Cross-sectional study. Four FKBP5 single-nucleotide polymorphisms used in previous studies (rs3800373, rs9296158, rs1360780, and rs9470080) were genotyped. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 60 publications
8
87
0
Order By: Relevance
“…Second, it is not clear whether the associations between FKBP5 SNPs and withdrawal severity may be attributed to other comorbid psychiatric disorders, such as major depression or PTSD. In addition, childhood trauma has been shown to interact with FKBP5 gene variation to influence the stress response (Binder et al, 2008;Roy et al, 2010;Xie et al, 2010;Bevilacqua et al, 2012) and is considered to be a confounding variable in HPA axis dysregulation in alcohol-dependent patients (Schafer et al, 2010). Therefore, we were unable to exclude the contribution from stressful life events to our results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Second, it is not clear whether the associations between FKBP5 SNPs and withdrawal severity may be attributed to other comorbid psychiatric disorders, such as major depression or PTSD. In addition, childhood trauma has been shown to interact with FKBP5 gene variation to influence the stress response (Binder et al, 2008;Roy et al, 2010;Xie et al, 2010;Bevilacqua et al, 2012) and is considered to be a confounding variable in HPA axis dysregulation in alcohol-dependent patients (Schafer et al, 2010). Therefore, we were unable to exclude the contribution from stressful life events to our results.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the minor alleles of rs9470080 and rs1360780 are associated with total cortisol secretion during the day expressed as the AUC (cortisol AUC ) (Velders et al, 2011). Finally, a haplotype of the above-listed SNPs has been associated with suicidal attempts (Roy et al, 2010) or aggressive behavior (Bevilacqua et al, 2012) among individuals with childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further support for this notion was provided by a study which showed that activation of GRs in dopamine receptor-expressing neurons in mesocorticolimbic and striatal circuits promoted social aversion induced by a subchronic social defeat procedure in mice 75 . Moreover, in humans, an interaction between genetic variation in the gene encoding FKBP5 (a cochaperone of heat shock protein 90 that affects the transcriptional capacity of GRs) and childhood trauma influences both lifetime history of aggressive behavior 76 and the glucocorticoid response to stress 77 . These findings suggest that individual differences in the neurodevelopmental trajectories leading to antisociality might be related to genetic variation in HPA-axis-related genes that affect the functioning of the stress systems during development and its consequent promotion of long-lasting epigenetic adaptations 76,78 .…”
Section: Effects Of Manipulating Glucocorticoid Levelsmentioning
confidence: 99%